Efeitos das queimadas nas doenças respiratórias humanas nos municípios de Altamira , Marabá e Santana do Araguaia no Estado do Pará - GOMES, Ana Carla dos Santos (2019)
The forest fire is one old agronomical or forest practice that uses the fire in a controlled form to make possible to agriculture renew the pastures. Three cities of the State of Pará had been studied: Altamira, Marabá and Santana of Araguaia to verify effect of the forest fires in the human health. With the use of the remote sensing Tool, through images of satellites, it was obtained these focus of heat (burnt) and used the data base of the System of Health - SUS, separate data of Internments for bands from 1 to 4 years and above of the 60 years, with the objective to identify and evaluate the correlation existence, between forest fires and respiratory illnesses. The results shown direct relation between the forest fires and the precipitation, that, in the less rainy months, August, September and October, when occurs forest fires in the studied cities. Correlation was also observed in a regularly time mainly with secular imbalance, where through the coefficient of determination, it showed the existence of significant correlation between years bands from 1 to 4 years for the three studied cities. In Santana of Araguaia and Marabá the correlation exists in the year band above of 60 years, whereas in the city of Altamira exits occurrence but does not stop the majority of the internments. With the biomass burning, innumerable particles and pollutant gases are sent to atmosphere, that, indirectly influence in a direct form in the human health, then, expects that this work contributes for the information level so that preventions can be taken for social and economic benefits of the region.